Evidence of recurrent selection of mutations commonly found in SARS-CoV-2 variants of concern in viruses infecting immunocompromised patients - Goes, Livia R.; Siqueira, Juliana D.; Garrido, Marianne M.; Alves, Brunna M.; Cicala, Claudia; Arthos, James; Viola, João P. B.; Soares, Marcelo A. (Frontiers in Microbiology, 2022)
Chronically-immunosuppressed patients infected with SARS-CoV-2 often experience prolonged virus shedding, and may pave the way to the emergence of mutations that render viral variants of concern (VOC) able to escape immune responses induced by natural infection or by vaccination. We report herein a SARS-CoV-2+ cancer patient from the beginning of the COVID-19 pandemic whose virus quasispecies across multiple timepoints carried several immune escape mutations found in more contemporary VOC, such as alpha, delta and omicron, that appeared to be selected for during infection. We hypothesize that immunosuppressed patients may represent the source of VOC seen throughout the COVID-19 pandemics.